Dielectric medium composite material and preparation method and application thereof
By 3D printing alternately stacked barium titanate layer and boron nitride layer, combined with resin composition and silicone compound, the problem of material performance degradation when dielectric ceramics and polymer composites are solved, the high dielectric constant and breakdown strength are improved, and the energy storage density is significantly improved.
Patent Information
- Application Number
- CN202411972215.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-30
AI Technical Summary
While the existing dielectric ceramics and polymer composite materials increase the dielectric constant, it is difficult to avoid degradation of material properties, especially the decrease in breakdown strength, which limits the further improvement of energy storage density.
By 3D printing alternately stacked barium titanate layer and boron nitride layer, the barium titanate layer has a three-dimensional mesh structure and is filled with a resin composition, and the ceramic skeleton is surface treated with silicone compounds to improve the excessive interfacial continuity of the material.
The dielectric constant and breakdown strength are improved, the internal defects of the material are avoided, and the energy storage density of the dielectric composite material is significantly improved.
Smart Images

Figure HDA0005219716660000011 
Figure HDA0005219716660000012 
Figure HDA0005219716660000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage dielectric materials, and in particular to a dielectric composite material and a preparation method and application thereof. Background Art
[0002] In the field of dielectric material science, dielectric ceramics have become the focus of research and application due to their excellent high dielectric constant characteristics. This type of material shows great potential in enhancing the energy storage performance of polymer-based composites, especially in the fields of capacitors, energy storage devices and high-frequency electronic devices. The preparation process of dielectric ceramic and polymer composites usually involves uniformly dispersing fine dielectric ceramic powders in a polymer matrix, aiming to effectively improve the overall dielectric constant of the composite material by introducing ceramic particles, thereby achieving enhanced energy storage density. However, the technical challenge is how to avoid the resulting degradation of material performance while ensuring a high dielectric constant. In order to pursue a higher dielectric constant, a large amount of ceramic powder is often required to be added to the polymer. The introduction of a large number of ceramic particles not only increases the difficulty of material processing, but also easily leads to agglomeration between particles and the formation of pores inside the material. The breakdown strength of the material is greatly weakened, that is, the ability of the material to withstand the maximum electric field strength without being destroyed. The reduction in breakdown strength directly limits the further improvement of the energy storage density of the composite material.
[0003] Chinese invention patent CN105541389B uses polyurethane sponge as carrier, and prepares ceramic / polymer composite material by constructing three-dimensional dielectric ceramic network, which not only solves the problem of poor molding process caused by high ceramic addition, but also can obtain high dielectric constant under lower ceramic content. However, the structure of this three-dimensional ceramic network depends on the carrier sponge of ceramic particles, and it is difficult to prepare the composite material with higher ceramic content, so the dielectric constant of composite material is limited. In addition, due to the different thermal expansion coefficients between ceramic skeleton and polymer (approximately 500 times different), stress cracking is prone to occur after molding and defects are formed, and these defects will greatly reduce the dielectric strength of the final composite material. Summary of the invention
[0004] The first aspect of the present invention provides a dielectric composite material, comprising alternately stacked barium titanate layers and boron nitride layers, wherein the barium titanate layers are three-dimensional network structures filled with a resin composition, and the barium titanate layers and the boron nitride layers are fixedly connected.
[0005] The number of layers of the barium titanate layer and the boron nitride layer are both 2-10.
[0006] Preferably, the number of layers of the barium titanate layer and the boron nitride layer are both 2-5.
[0007] The components of the resin composition include epoxy resin, barium titanate and epoxy curing agent.
[0008] The amount of barium titanate added to the resin composition is 2-10 wt %.
[0009] Preferably, the amount of barium titanate added to the resin composition is 3-8 wt %.
[0010] Preferably, the epoxy resin comprises bisphenol A type epoxy resin.
[0011] This application study found that by 3D printing alternately stacked barium titanate layers and boron nitride layers, the barium titanate layer is a three-dimensional network structure, and the three-dimensional network structure is filled with a resin composition, which can improve the dielectric constant and enhance its breakdown strength. Further research found that the components of the resin composition include epoxy resin, barium titanate and epoxy curing agent, and the ceramic skeleton is surface treated with organic silicon compounds. It can improve the excessive continuity of the interface of the dielectric composite material and avoid the generation of defects. It may be that the specific barium titanate and surface treatment solve the internal defects caused by the difference in thermal expansion coefficients between the skeleton and the resin matrix, thereby avoiding stress cracking after molding and forming defects.
[0012] The epoxy curing agent includes an amine curing agent, and the amine curing agent includes diethylenetriamine, ethylenediamine, triethylenetetramine, 1,6-hexanediamine, tetraethylenepentamine, 4-amino-α,α-4-trimethyl-cyclohexanemethylamine, 5-amino-1,3,3-trimethylcyclohexanemethylamine, bis(4-amino-3-methylcyclohexyl)methane, bis(4-aminocyclohexyl)methane, 3,3'-dimethyl-4,4-diaminodicyclohexylmethane, 4,4'-diaminodicyclohexylmethane, 4,4'-methylenebis( At least one of 2-methyl-6-ethylaniline), m-phenylenediamine, m-phenylenediamine, 4,4-diaminodiphenyl sulfone, 4,4-diaminodiphenylmethane, diethyltoluenediamine, dimethylthiotoluenediamine, 3-chloro-3'-ethyl-4,4'-diaminodiphenylmethane, 4,4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-ethyl)aniline, 4,4'-bis-sec-butylaminodiphenylmethane, and 4,4'-methylenebis(3-chloro-2,6-diethylaniline).
[0013] The raw materials for preparing the barium titanate layer include micron barium titanate and nano barium titanate, and the weight ratio of the micron barium titanate to the nano barium titanate is 1:(1.5-6).
[0014] Preferably, the weight ratio of the micron barium titanate to the nano barium titanate is 1:(1.5-4).
[0015] Further preferably, the weight ratio of the micron barium titanate to the nano barium titanate is 1:(1.5-2).
[0016] Preferably, the particle size of the micronized barium titanate is not greater than 10 μm.
[0017] Further preferably, the particle size of the micron barium titanate is not greater than 5 μm.
[0018] Preferably, the particle size of the nano-barium titanate is not greater than 500 nm.
[0019] Further preferably, the particle size of the nano-barium titanate is not higher than 200 nm.
[0020] The raw material for preparing the boron nitride layer includes boron nitride with a particle size not greater than 500 nm.
[0021] Preferably, the raw material for preparing the boron nitride layer includes boron nitride with a particle size not greater than 300 nm.
[0022] Preferably, the raw materials for preparing the barium titanate layer and the boron nitride layer also include a photosensitive resin mixed solution and an organic silicon compound.
[0023] A second aspect of the present invention provides a method for preparing a dielectric composite material, comprising the following steps:
[0024] The micronized barium titanate and the nanometer barium titanate are mixed with a photosensitive resin mixed solution to obtain a barium titanate slurry; the boron nitride is mixed with the photosensitive resin mixed solution to obtain a boron nitride slurry;
[0025] Using barium titanate slurry and boron nitride slurry for 3D printing to obtain alternatingly stacked barium titanate green body layers and boron nitride green body layers;
[0026] Sintering the alternately stacked barium titanate green layers and boron nitride green layers to obtain a ceramic skeleton;
[0027] Using an organic silicon compound to treat the surface of the ceramic skeleton to obtain a silane-modified ceramic skeleton;
[0028] The silane-modified ceramic skeleton is mixed with components of the resin composition and cured to obtain a dielectric composite material.
[0029] The addition amount of barium titanate in the barium titanate slurry is 50-80wt%.
[0030] Preferably, the amount of barium titanate added to the barium titanate slurry is 60-80 wt %.
[0031] The amount of boron nitride added to the boron nitride slurry is 30-60 wt %.
[0032] Preferably, the amount of boron nitride added to the boron nitride slurry is 40-50 wt %.
[0033] The organic silicon compound includes a silane coupling agent.
[0034] Preferably, the silane coupling agent includes at least one of the following brands: KH-550, KH-551, KH-560, KH-570, A-151, A-171.
[0035] The photosensitive resin mixed liquid comprises: photosensitive resin, initiator and auxiliary agent.
[0036] The photosensitive resin includes difunctional acrylate, hydroxy acrylate monomer, trifunctional acrylate and acrylic phosphate.
[0037] The acrylic acid phosphate includes methacrylic acid phosphate, hydroxyethyl methacrylic acid phosphate, 2-methyl-2-hydroxyethyl acrylic acid phosphate
[0038] The hydroxy acrylate monomer includes at least one of ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, hydroxypropyl acrylate, and hydroxybutyl acrylate.
[0039] The bifunctional acrylate includes at least one of 1,6-hexanediol diacrylate, triethylene glycol dimethacrylate and tripropylene glycol diacrylate.
[0040] The trifunctional acrylate includes SR9051 NS (Sartomer).
[0041] The auxiliary agents include a leveling agent and a thickener.
[0042] Preferably, the leveling agent includes BYK307; and the thickener includes SA-6000.
[0043] The initiator includes one or more of benzoin dimethyl ether, benzophenone, 1-hydroxycyclohexyl phenyl ketone (abbreviated as: 184 photoinitiator), 2-hydroxy-2-methyl-1-phenyl-1-propanone (abbreviated as: 1173 photoinitiator), 2-methyl-1-(4-methylthio)phenyl-2-morpholinylpropyl-1-ketone (IRGACURE 907), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (abbreviated as: TPO photoinitiator), 2,4,6-trimethylbenzoylphosphonic acid ethyl ester phenyl (abbreviated as: TPO-L photoinitiator), and bis(2,4,6-trimethylbenzoyl)phosphine oxide (IRGACURE 819).
[0044] The sintering temperature is 1100-1400° C., and the sintering time is 2-5 hours.
[0045] Preferably, the sintering temperature is 1250-1350° C., and the sintering time is 2-4 hours.
[0046] The surface treatment steps include: the ceramic skeleton is first reacted with hydrogen peroxide, then impregnated with an organic solvent, and then modified with a silane coupling agent.
[0047] A third aspect of the present invention provides an application of a method for preparing a dielectric composite material, which is applied to the preparation of capacitors.
[0048] Beneficial Effects
[0049] 1. By 3D printing, alternately stacked barium titanate layers and boron nitride layers are formed, wherein the barium titanate layers are a three-dimensional network structure, and the three-dimensional network structure is filled with a resin composition, which can improve the dielectric constant and enhance its breakdown strength.
[0050] 2. The components of the resin composition include epoxy resin, barium titanate and epoxy curing agent, and the organic silicon compound is used to treat the surface of the ceramic skeleton, which can improve the interface continuity of the dielectric composite material and avoid the generation of defects.
[0051] 3. The raw materials for preparing the barium titanate layer include micron barium titanate and nano barium titanate, and the weight ratio of the micron barium titanate to the nano barium titanate is 1:(1.5-6), which can further improve the energy storage density of the dielectric composite material.
[0052] 4. The weight ratio of micron barium titanate to nano barium titanate is 1:(1.2-4), and the energy storage density can exceed 12J / cm 3 , to meet the use requirements of capacitors.
[0053] 5. The preparation process of this application is simple and the raw materials are easily available. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The dielectric composite material was prepared according to Example 1.
[0055] Figure 2 The dielectric composite material was prepared according to Example 2.
[0056] Figure 3 The dielectric composite material was prepared in Comparative Example 1.
[0057] Figure 4 This is an electron microscope image of the interface (interlayer junction) of the dielectric composite material prepared in Example 1.
[0058] Figure 5 This is an electron microscope image of the interface (interlayer junction) of the dielectric composite material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0059] Example 1
[0060] A dielectric composite material, such as Figure 1 As shown, barium titanate layers and boron nitride layers are alternately stacked (a 5-layer structure, from top to bottom, boron nitride layer-barium titanate layer-boron nitride layer-barium titanate layer-boron nitride layer), the barium titanate layer is a three-dimensional network structure, the three-dimensional network structure is filled with a resin composition, and the barium titanate layer and the boron nitride layer are fixedly connected by sintering.
[0061] A method for preparing a dielectric composite material comprises the following steps:
[0062] 35 g of 1 μm barium titanate (Shanghai Aladdin Biochemical Technology Co., Ltd.) and 105 g of 100 nm barium titanate (Shanghai McLean Biochemical Technology Co., Ltd.) were added to 60 g of the photosensitive resin mixture, and the mixture was ball-milled for 2 h to obtain barium titanate slurry; 45 g of boron nitride (200 nm, Shanghai McLean Biochemical Technology Co., Ltd.) was added to 55 g of the photosensitive resin mixture, and the boron nitride slurry was obtained by ball-milling for 1 h.
[0063] 3D printing (commercial DLP 3D printer) was performed using barium titanate slurry and boron nitride slurry, with a printing layer thickness of 20 μm and a single layer exposure time of 10 s to obtain alternating stacked barium titanate green layers and boron nitride green layers;
[0064] The alternately stacked barium titanate green layers and boron nitride green layers are sintered (in a muffle furnace, the temperature is raised to 1300°C at a rate of 1°C / min and kept at this temperature for 3 hours) to obtain a ceramic skeleton;
[0065] The ceramic skeleton was immersed in a 30wt% hydrogen peroxide solution and refluxed at 80°C for 3h. After the reaction, it was washed with deionized water, immersed in n-propanol, 0.2mol of KH560 and 0.26mol of deionized water were added, and stirred at 60°C for 1h. Then, the pH value of the mixture was adjusted to 10 with a 1wt% n-propanol solution of NaOH, and the reaction was continued at this temperature for 6h. After being fully washed with ethanol and dried, a hyperbranched polysiloxane-modified ceramic skeleton was obtained.
[0066] The hyperbranched polysiloxane-modified ceramic skeleton was mixed with the components of the resin composition (5wt% barium titanate, 10wt% triethylenetetramine, 85wt% epoxy resin NPEL-128 (Nanya Epoxy Resin Kunshan Co., Ltd.)), and degassed in a vacuum oven for multiple times until no bubbles were generated. Finally, it was cured at room temperature for 24 hours and transferred to a 100°C forced air drying oven for 4 hours to obtain a dielectric composite material.
[0067] Preparation of the photosensitive resin mixture: Under light protection, 1,6-ethylene glycol diacrylate, trimethylolpropane triacrylate, trifunctional acid ester SR9051 NS (Sartomer, Shengjia Enterprise Co., Ltd.), 2-methyl-2-hydroxyethyl acrylate phosphate, BYK307, SA-6000, and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide are mixed in a ratio of 63wt%: 21.2wt%: 6.5wt%: 2wt%: 3wt%: 2.5wt%: 1.8wt%.
[0068] Example 2
[0069] A dielectric composite material, such as Figure 2 As shown, there are alternately stacked barium titanate layers and boron nitride layers (a 7-layer structure, from top to bottom: barium titanate layer-boron nitride layer-barium titanate layer-boron nitride layer-barium titanate layer-boron nitride layer-barium titanate layer), the barium titanate layer is a three-dimensional network structure, the three-dimensional network structure is filled with a resin composition, and the barium titanate layer and the boron nitride layer are fixedly connected by sintering.
[0070] A method for preparing a dielectric composite material comprises the following steps:
[0071] 50 g of 1 μm barium titanate (Shanghai Aladdin Biochemical Technology Co., Ltd.) and 90 g of 100 nm barium titanate (Shanghai McLean Biochemical Technology Co., Ltd.) were added to 60 g of the photosensitive resin mixture, and the mixture was ball-milled for 2 h to obtain barium titanate slurry; 45 g of boron nitride (200 nm, Shanghai McLean Biochemical Technology Co., Ltd.) was added to 55 g of the photosensitive resin mixture, and the boron nitride slurry was obtained by ball-milling for 1 h.
[0072] 3D printing (commercial DLP 3D printer) was performed using barium titanate slurry and boron nitride slurry, with a printing layer thickness of 20 μm and a single layer exposure time of 10 s to obtain alternating stacked barium titanate green layers and boron nitride green layers;
[0073] The alternately stacked barium titanate green layers and boron nitride green layers are sintered (in a muffle furnace, the temperature is raised to 1300°C at a rate of 1°C / min and kept at this temperature for 3 hours) to obtain a ceramic skeleton;
[0074] The ceramic skeleton was immersed in a 30wt% hydrogen peroxide solution and refluxed at 80°C for 3h. After the reaction, it was washed with deionized water, immersed in n-propanol, 0.2mol of KH560 and 0.26mol of deionized water were added, and stirred at 60°C for 1h. Then, the pH value of the mixture was adjusted to 10 with a 1wt% n-propanol solution of NaOH, and the reaction was continued at this temperature for 6h. After being fully washed with ethanol and dried, a hyperbranched polysiloxane-modified ceramic skeleton was obtained.
[0075] The hyperbranched polysiloxane-modified ceramic skeleton was mixed with the components of the resin composition (5wt% barium titanate, 10wt% triethylenetetramine, 85wt% epoxy resin NPEL-128 (Nanya Epoxy Resin Kunshan Co., Ltd.)), and degassed in a vacuum oven for multiple times until no bubbles were generated. Finally, it was cured at room temperature for 24 hours and transferred to a 100°C forced air drying oven for 4 hours to obtain a dielectric composite material.
[0076] Preparation of the photosensitive resin mixture: Under light protection, 1,6-ethylene glycol diacrylate, trimethylolpropane triacrylate, trifunctional acid ester SR9051 NS (Sartomer, Shengjia Enterprise Co., Ltd.), 2-methyl-2-hydroxyethyl acrylate phosphate, BYK307, SA-6000, and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide are mixed in a ratio of 63wt%: 21.2wt%: 6.5wt%: 2wt%: 3wt%: 2.5wt%: 1.8wt%.
[0077] Comparative Example 1
[0078] A dielectric composite material, such as Figure 3 As shown, stacked barium titanate layers are sintered (four-layer structure), and the barium titanate layers are three-dimensional network structures filled with a resin composition.
[0079] A method for preparing a dielectric composite material comprises the following steps:
[0080] 50 g of 1 μm barium titanate (Shanghai Aladdin Biochemical Technology Co., Ltd.) and 90 g of 100 nm barium titanate (Shanghai MacLean Biochemical Technology Co., Ltd.) were added to 60 g of the photosensitive resin mixture and ball-milled for 2 h to obtain barium titanate slurry.
[0081] 3D printing (commercial DLP 3D printer) using barium titanate slurry with a printing layer thickness of 20 μm and a single layer exposure time of 10 s to obtain a stacked barium titanate green body layer;
[0082] The stacked barium titanate green layers were sintered (muffle furnace, heating to 1300°C at a rate of 1°C / min and kept at this temperature for 3 hours) to obtain a ceramic skeleton;
[0083] The ceramic skeleton was immersed in a 30wt% hydrogen peroxide solution and refluxed at 80°C for 3h. After the reaction, it was washed with deionized water, immersed in n-propanol, 0.2mol of KH560 and 0.26mol of deionized water were added, and stirred at 60°C for 1h. Then, the pH value of the mixture was adjusted to 10 with a 1wt% n-propanol solution of NaOH, and the reaction was continued at this temperature for 6h. After being fully washed with ethanol and dried, a hyperbranched polysiloxane-modified ceramic skeleton was obtained.
[0084] The hyperbranched polysiloxane-modified ceramic skeleton was mixed with the components of the resin composition (5wt% barium titanate, 10wt% triethylenetetramine, 85wt% epoxy resin NPEL-128 (Nanya Epoxy Resin Kunshan Co., Ltd.)), and degassed in a vacuum oven for multiple times until no bubbles were generated. Finally, it was cured at room temperature for 24 hours and transferred to a 100°C forced air drying oven for 4 hours to obtain a dielectric composite material.
[0085] Preparation of the photosensitive resin mixture: Under light protection, 1,6-ethylene glycol diacrylate, trimethylolpropane triacrylate, trifunctional acid ester SR9051 NS (Sartomer, Shengjia Enterprise Co., Ltd.), 2-methyl-2-hydroxyethyl acrylate phosphate, BYK307, SA-6000, and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide are mixed in a ratio of 63wt%: 21.2wt%: 6.5wt%: 2wt%: 3wt%: 2.5wt%: 1.8wt%.
[0086] Comparative Example 2
[0087] A dielectric composite material is formed by sintering stacked barium titanate layers (four-layer structure), wherein the barium titanate layers are three-dimensional network structures filled with a resin composition.
[0088] A method for preparing a dielectric composite material comprises the following steps:
[0089] 50 g of 1 μm barium titanate (Shanghai Aladdin Biochemical Technology Co., Ltd.) and 90 g of 100 nm barium titanate (Shanghai MacLean Biochemical Technology Co., Ltd.) were added to 60 g of the photosensitive resin mixture and ball-milled for 2 h to obtain barium titanate slurry.
[0090] 3D printing (commercial DLP 3D printer) using barium titanate slurry with a printing layer thickness of 20 μm and a single layer exposure time of 10 s to obtain a stacked barium titanate green body layer;
[0091] The stacked barium titanate green layers were sintered (muffle furnace, heating to 1300°C at a rate of 1°C / min and kept at this temperature for 3 hours) to obtain a ceramic skeleton;
[0092] The ceramic skeleton was mixed with the components of the resin composition (5wt% barium titanate, 10wt% triethylenetetramine, 85wt% epoxy resin NPEL-128 (Nan Ya Epoxy Resin Kunshan Co., Ltd.)), and degassed in a vacuum oven for multiple times until no bubbles were generated. Finally, it was cured at room temperature for 24 hours and transferred to a 100°C forced air drying oven for 4 hours to obtain a dielectric composite material.
[0093] Preparation of the photosensitive resin mixture: Under light protection, 1,6-ethylene glycol diacrylate, trimethylolpropane triacrylate, trifunctional acid ester SR9051 NS (Sartomer, Shengjia Enterprise Co., Ltd.), 2-methyl-2-hydroxyethyl acrylate phosphate, BYK307, SA-6000, and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide are mixed in a ratio of 63wt%: 21.2wt%: 6.5wt%: 2wt%: 3wt%: 2.5wt%: 1.8wt%.
[0094] Performance Testing Methods
[0095] The dielectric composite materials prepared in the examples and comparative examples were tested for energy storage density, and the test data are listed in Table 1.
[0096] The energy storage density is calculated by testing the hysteresis loop of the material in accordance with GB / T 6426-1999 (quasi-static test method for hysteresis loop of ferroelectric ceramic materials).
[0097] The interfaces of the dielectric composite materials prepared in Example 1 and Comparative Example 1 were tested by electron microscopy. Figure 4 As shown, the interface bonding is good, and Figure 5 Cracks appear at the interface.
[0098] Performance test data
[0099] Table 1
[0100] sample <![CDATA[Energy storage density (J / cm 3 )]]> Example 1 12.21 Example 2 16.85 Comparative Example 1 2.42 Comparative Example 2 2.16
Claims
1. A dielectric composite material, characterized in that: The invention comprises alternately stacked barium titanate layers and boron nitride layers, wherein the barium titanate layers are three-dimensional network structures filled with a resin composition, and the barium titanate layers and the boron nitride layers are fixedly connected.
2. The dielectric composite material according to claim 1, characterized in that: The number of layers of the barium titanate layer and the boron nitride layer are both 2-10.
3. The dielectric composite material according to claim 2, characterized in that: The components of the resin composition include epoxy resin, barium titanate and epoxy curing agent.
4. The dielectric composite material according to claim 3, characterized in that: The amount of barium titanate added to the resin composition is 2-10 wt %.
5. The dielectric composite material according to claim 1, characterized in that: The raw materials for preparing the barium titanate layer include micron barium titanate, nano barium titanate, organic silicon compound and photosensitive resin mixed solution, and the weight ratio of the micron barium titanate to the nano barium titanate is 1:(1.5-6).
6. The dielectric composite material according to claim 5, characterized in that: The raw materials for preparing the boron nitride layer include boron nitride with a particle size not greater than 500nm, an organic silicon compound and a photosensitive resin mixed solution.
7. A method for preparing the dielectric composite material according to claim 6, characterized in that: The following steps are involved: The micronized barium titanate and the nanometer barium titanate are mixed with a photosensitive resin mixed solution to obtain a barium titanate slurry; the boron nitride is mixed with the photosensitive resin mixed solution to obtain a boron nitride slurry; Using barium titanate slurry and boron nitride slurry for 3D printing to obtain alternatingly stacked barium titanate green body layers and boron nitride green body layers; Sintering the alternately stacked barium titanate green layers and boron nitride green layers to obtain a ceramic skeleton; Using an organic silicon compound to treat the surface of the ceramic skeleton to obtain a silane-modified ceramic skeleton; The silane-modified ceramic skeleton is mixed with components of the resin composition and cured to obtain a dielectric composite material.
8. The method for preparing the dielectric composite material according to claim 7, characterized in that: The organic silicon compound includes a silane coupling agent.
9. The method for preparing the dielectric composite material according to claim 8, characterized in that: The surface treatment steps include: the ceramic skeleton is first reacted with hydrogen peroxide, then impregnated with an organic solvent, and then modified with a silane coupling agent.
10. An application of the method for preparing a dielectric composite material according to any one of claims 7 to 9, characterized in that: Used in the preparation of capacitors.
Citation Information
Patent Citations
A kind of barium titanate foam ceramics / thermosetting resin composite material and preparation method thereof
CN105541389B
Polymer matrix composite material containing filler particle three-dimensional network and preparation method thereof
CN108250677A
Preparation method of barium titanate-based ceramic slurry for photocuring 3D printing
CN113716955A
Three-dimensional periodical structural body and method of manufacturing the same
JP2003337201A